2018
DOI: 10.5624/isd.2018.48.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint synovial chondromatosis accompanying temporal bone proliferation: A case report

Abstract: Synovial chondromatosis is a rare metaplastic disease affecting the joints, including the temporomandibular joint (TMJ). Since its symptoms are similar to those of temporomandibular disorders, a careful differential diagnosis is essential. A 50-year-old male patient was referred with the chief complaint of pain and radiopaque masses around the left TMJ on panoramic radiography. Clinically, pre-auricular swelling and resting pain was found, without limitation of mouth opening. On cone-beam computed tomographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“… 11 , 28 T2WI of MRI has an important reference value for the diagnosis of SC in the TMJ, which mainly manifests as a synovial thickening, joint capsule expansion, cartilage nodules, or calcified loose bodies showing low signal intensity scattered in the effusion that present high signal intensity. 30 , 31 MRI could be a reliable diagnostic tool in the diagnosis of SC in the TMJ as its estimated diagnostic accuracy is nearly 96.06%. 32 In case 1 of this study, the CBCT image showed a widened joint cavity space, and one ineffective injection treatment made the clinician aware of the possibility of SC.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 28 T2WI of MRI has an important reference value for the diagnosis of SC in the TMJ, which mainly manifests as a synovial thickening, joint capsule expansion, cartilage nodules, or calcified loose bodies showing low signal intensity scattered in the effusion that present high signal intensity. 30 , 31 MRI could be a reliable diagnostic tool in the diagnosis of SC in the TMJ as its estimated diagnostic accuracy is nearly 96.06%. 32 In case 1 of this study, the CBCT image showed a widened joint cavity space, and one ineffective injection treatment made the clinician aware of the possibility of SC.…”
Section: Discussionmentioning
confidence: 99%
“…9,23,29e31 Regarding the popcorn calcification type, the shape is actually more similar to a crescent enveloping the mandibular condyle (Figs 2d, 7a, 7b, 7d, 7e) rather than a circle on an axial plane, which is also consistent with a previous report. 32 The reason for this type of calcification forming a crescent shape may be that the involved nodules are conglomerated in an environment where the joint space is narrow and the condyle impacts the calcification formation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, radiological imaging is the key to differentiate between these two different conditions. SC more often occurs in superior articulation cavity, generally involves rounder loose bodies and usually shows regular configuration of mandibular condyle associated with expansion and effusion of the joint cavity [9]. Degenerative joint disease, instead, usually occurs in inferior articulation cavity, involves angular loose bodies and generally presents evident degenerative modifications of the mandibular condyle, frequently associated with osteophytes [9].…”
Section: Discussionmentioning
confidence: 99%